2013
DOI: 10.1186/1472-6920-13-65
|View full text |Cite
|
Sign up to set email alerts
|

An electronic portfolio for quantitative assessment of surgical skills in undergraduate medical education

Abstract: BackgroundWe evaluated a newly designed electronic portfolio (e-Portfolio) that provided quantitative evaluation of surgical skills. Medical students at the University of Seville used the e-Portfolio on a voluntary basis for evaluation of their performance in undergraduate surgical subjects.MethodsOur new web-based e-Portfolio was designed to evaluate surgical practical knowledge and skills targets. Students recorded each activity on a form, attached evidence, and added their reflections. Students self-assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 25 publications
0
37
0
6
Order By: Relevance
“…Several studies [7,9,11,22,23] have advocated that e-portfolios are particularly useful as a record of experience and promotes independent reflective learning, to think back about those experiences. The record can be in the form of a logbook or a diary of day to day work experiences, [5,6] which is especially important in the highly skills-dependent healthcare profession where the learning takes place in a working clinical environment as opposed to a classroom teaching basis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies [7,9,11,22,23] have advocated that e-portfolios are particularly useful as a record of experience and promotes independent reflective learning, to think back about those experiences. The record can be in the form of a logbook or a diary of day to day work experiences, [5,6] which is especially important in the highly skills-dependent healthcare profession where the learning takes place in a working clinical environment as opposed to a classroom teaching basis.…”
Section: Discussionmentioning
confidence: 99%
“…The record can be in the form of a logbook or a diary of day to day work experiences, [5,6] which is especially important in the highly skills-dependent healthcare profession where the learning takes place in a working clinical environment as opposed to a classroom teaching basis. [24] Several studies [9,11,13] have also found that trainees prefer an electronic interface of managing a portfolio, stating it to be better suited to the active way of work in a clinical environment. In the UK, electronic portfolio interface is now readily available to clinicians and trainee doctors by most institutes and Royal Colleges, [5,6] and even generic ones are freely available by various organisation that cater to the medical profession as a whole, for example the BMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entre as competências essenciais na prática clíni-ca, temos a comunicação clínica e o profissionalismo, para os quais o OSCE tem sido um método utlizado com certa frequência e com bons resultados em alguns estudos [17][18][19][20] . Entre suas aplicações, tem a capacidade de avaliar a anamnese, o exame físico e a interpretação de resultados clínicos, com destaque para a comunicação efetiva 9,13 .…”
Section: Introductionunclassified